Síndrome Coronária Aguda sem elevação do segmento ST: duração do QRS e prognóstico a longo prazo - Rocha, S (2009)
BACKGROUND: Recent studies have demonstrated that QRS duration (QRSd) is associated with poor prognosis in heart failure and ST-elevation myocardial infarction. Less is known about the prognostic importance of QRSd in patients with non-ST elevation acute coronary syndrome (non-ST ACS). AIM: To determine if admission QRSd is associated with 1-year mortality in non-ST ACS. METHODS: We studied 539 patients (aged 65.52 +/- 12.47 years, 69.9% male) admitted to the coronary unit with non-ST ACS. QRSd was measured on the admission electrocardiogram. RESULTS: Mean QRSd was 94.29 +/- 18.3 ms. One-year mortality was 13.4%. QRSd showed a good correlation with 1-year mortality and its best cut-off was 92 ms. Patients with QRSd > or = 92 ms were older, more frequently male and with prior history of coronary heart disease. On admission they presented more often in Killip class > 1, and had a higher incidence of heart failure and left ventricular systolic dysfunction. They less often underwent coronary angiography. One-year mortality was higher in patients with QRSd > or = 92 ms. After adjusting for baseline characteristics and treatment, QRSd > or = 92 ms remained an independent predictor of 1-year mortality (adjusted OR=3.87; 95% CI 1.74-8.44). CONCLUSION: In this non-ST ACS population, QRSd was an independent predictor of 1-year mortality after the event.